PREVALENCE AND PATTERN OF MALOCCLUSION AMONG PATIENTS IN SATNA MADHYA PRADESH: A CROSS-SECTIONAL STUDY BASED ON DEWEY’S MODIFICATION - Dr. Monica Chaurasia; Dr. Ambrish Mishra; Divashree Sharma (Student's Journal of Health Research Africa, 2024)
Aim This study aimed to evaluate the prevalence and distribution of malocclusion among the patients reporting to the dental outpatient department (OPD) of the affiliated hospital of a Medical College in M.P. Materials and methods This cross-sectional study included 383 individuals aged 14–30 years who satisfied the inclusion criteria. Inclusion criteria consisted of the presence of all permanent teeth with or without third molars. The occlusal relationships were recorded in the centric occlusion position (COP). The occlusion traits were assessed as normal occlusion or malocclusion using the first permanent molars as described by E.H. Angle and deviation from the line of occlusion. The mean and proportions of the data were calculated using descriptive statistics. Results The prevalence of malocclusion in individuals aged 14–30 years was 60.84% (116 males and 117 females) Angle’s Class I malocclusion (41.77%) was more common among the individuals than Angle’s Class II malocclusion (15.40%) and Angle’s Class III malocclusion (3.67%). The distribution of Class II Division 1 was 11.75%, whereas Class II Division 2 was 3.65%. Dewey’s Class I type 1 was identified as the most common malocclusion. The prevalence of normal occlusion (as described by Angle) was 39.16% (116 males and 117 females) Conclusion Angle’s Class I malocclusion was the most prevalent in participants followed by normal occlusion as described by Angle. Dewey’s Class I type 1 was observed to be the most common malocclusion and Dewey’s Class III type 3 was the least observed type of malocclusion. Recommendations To develop a systematic and well-organized dental health care program in a community, basic information such as epidemiological studies on orthodontic malocclusion is required. This study is therefore useful for future studies on the prevalence of malocclusions in the Vindhya region of Madhya Pradesh (M.P.)